Co-occurrence of Hyperacusis Accelerates With Tinnitus Burden Over Time and Requires Medical Care - Refat, Fatma; Wertz, Jakob; Hinrichs, Pauline; Klose, Uwe; Samy, Hesham; Abdelkader, Rafeek Mohamed; Saemisch, Jörg; Hofmeier, Benedikt; Singer, Wibke; Rüttiger, Lukas; Knipper, Marlies; Wolpert, Stephan (Frontiers in Neurology, 2021)
Although tinnitus represents a major global burden, no causal therapy has yet been established. Ongoing controversies about the neuronal pathophysiology of tinnitus hamper efforts in developing advanced therapies. Hypothesizing that the unnoticed co-occurrence of hyperacusis and differences in the duration of tinnitus may possibly differentially influence the neural correlate of tinnitus, we analyzed 33 tinnitus patients without (T-group) and 20 tinnitus patients with hyperacusis (TH-group). We found crucial differences between the T-group and the TH-group in the increase of annoyance, complaints, tinnitus loudness, and central neural gain as a function of tinnitus duration. Hearing thresholds did not differ between T-group and TH-group. In the TH-group, the tinnitus complaints (total tinnitus score) were significantly greater from early on and the tinnitus intensity distinctly increased over time from ca. 12 dB to 17 dB when tinnitus persisted more than 5 years, while annoyance responses to normal sound remained nearly constant. In contrast, in the T-group tinnitus complaints remained constant, although the tinnitus intensity declined over time from ca. 27 dB down to 15 dB beyond 5 years of tinnitus persistence. This was explained through a gradually increased annoyance to normal sound over time, shown by a hyperacusis questionnaire. Parallel a shift from a mainly unilateral (only 17% bilateral) to a completely bilateral (100%) tinnitus percept occurred in the T-group, while bilateral tinnitus dominated in the TH-group from the start (75%). Over time in the T-group, ABR wave V amplitudes (and V/I ratios) remained reduced and delayed. By contrast, in the TH group especially the ABR wave III and V (and III/I ratio) continued to be enhanced and shortened in response to high-level sound stimuli. Interestingly, in line with signs of an increased co-occurrence of hyperacusis in the T-group over time, ABR wave III also slightly increased in the T-group. The findings disclose an undiagnosed co-occurrence of hyperacusis in tinnitus patients as a main cause of distress and the cause of complaints about tinnitus over time. To achieve urgently needed and personalized therapies, possibly using the objective tools offered here, a systematic sub-classification of tinnitus and the co-occurrence of hyperacusis is recommended.